Knowledge and Awareness of Hepatitis among Dental Fraternity in Udaipur- An Institutional Study - Pathak, Ayushi; Khichi, Swarnima; Singh, Rajendra; Joshi, Reenu; Sanadhya, Sudhanshu; Sharma, Manish (Journal of Neonatal Surgery, 2025)
Background- Hepatitis is one of the major infectious viral diseases of the world affecting mankind. It is the most common cause for liver cirrhosis and hepato-cellular carcinoma in the World. Possible forms of transmission of Hepatitis include unprotected sexual practises, reuse of contaminated needles and vertical transmission during pregnancy. Dental professionals are at a higher risk of Hepatitis infection due to their frequent exposure to contaminated blood, blood-soaked cottons, mucous membrane, saliva, gingival crevicular fluid and needle prick injuries. Hence’ placed in the high-risk group. There is no adequate data on the awareness of hepatitis among dental fraternity. Aim- To determine knowledge and awareness among the dental fraternity of Udaipur about hepatitis infection, its transmission, precautions and vaccine related. Methodology- Study was conducted in May 2024 at Darshan Dental College and Hospital, Udaipur on 307 participants of dental fraternity. Inclusion and Exclusion criterias were taken in consideration. Questionnaire link through Google forms were shared among participants. Questions had three options (yes/no/maybe). The noted data was compiled and analysed using Microsoft Excel 2010 and SPSS version 26. Results- More than 248 (81%) participants agreed on the fact that dental fraternity is at more risk of Hepatitis infection than any other healthcare sector and Hepatitis is the most common occupational hazards among dentists worldwide. Conclusion- Dental professionals’ knowledge of Hepatitis infection, the probable routes of its transmission during dental treatment, and the most effective preventive strategies against it may be a great help in preventing the spread of this infection.